State-Aiding, Empire-Building or Multitude Fulfilling? An Anonymous Role in International Politics - Tynes, Robert M (AoIR Selected Papers of Internet Research, 2016)
GhostSec is out there, fighting. The Anonymous cell is hack-attacking politicallyviolent Islamic groups, including Al-Shabaab, Boko Haram and the Islamic State(IS). GhostSec is intent upon exposing extremist twitter accounts and takingdown their web face presence. The goal seems to be to prevent the "bad guys"from using cybertools to perpetuate their violence in Somalia, Nigeria, Libya andSyria. As such, GhostSec is a humanitarian cause that prevents theterritorialization of cyberspace by those groups who are against the liberalideology of freedom of the individual. It is a noble cause, a cyber battle, almostmythic. Is it so simple, though--good vs. bad? And what is the desired outcome?This article will explore the role of GhostSec in international politics, specificallyexamining whether the Anonymous group is State-Aiding, Empire-Building orMultitude-Fulfilling (Hardt and Negri 2000). Even though the trickster lulzAnonymous may jump out and raspberry the world while it "takes down" aterrorist group's web body, it still must consider the socio-political forces vyingfor the power that it generates. Who benefits from its antics, who loses?